Correlation and path analysis in relation to seed yield and its components in Indian mustard (Brassica juncea L. Czern and Coss): Correlation and path analysis in relation to seed yield and its components in Indian mustard (Brassica juncea L. Czern and Coss) - J R PATEL; A T SAIYAD; K P PRAJAPATI; B K PATEL; P J PATEL (Journal of Oilseeds Research, 2020)
Sixty diverse genotypes of Indian mustard [Brassica juncea (L.) Czern & Coss.] were evaluated for 17 quantitative and qualitative traits. Association analysis revealed that seed yield/plant was significantly correlated with plant height, number of branches/plant, number of siliqua/plant, seeds/siliqua, length of siliqua, 1000-seed weight, oil content, linolenic acid and erucic acid. Days to flowering and days to maturity was negatively correlated with seed yield/plant. Path coefficient analysis indicated the highest positive direct effect on seed yield/plant by oil content followed by days to flowering, linoleic acid, number of branches/plant, 1000-seed weight, length of siliqua, days to maturity and stearic acid. The character oleic acid exerted the highest negative direct effect on seed yield/plant.